Studi Potensi Radiasi Matahari Untuk Pemanfaatan Energi Surya Di Kota Kendari - Wiwin, Andi; Kadir, Abd; Hasanudin, La; Galugu, Indrayati (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
The purpose of this research is to know the data of solar radiation intensity that will be used in the utilization of solar energy. The tools and materials used in this research are Solar Power Meter, HP android, laptop, and thermometer. From the results of research can be concluded some things that data about the intensity of solar radiation can be obtained by using two methods of direct measurement and theoretical calculation. Solar intensity data obtained in this study by taking the average value of data research for a month exactly month march 2018, then obtained value for the measurement directly with the highest value of solar radiation intensity data is at 11:30 with the sun radiation intensity value of 666 W/m2 and the lowest value of solar radiation intensity data is at 17:00 with the sun radiation intensity value 167 W/m2, while for theoretical calculation then obtained with the highest value of solar radiation intensity data is at 12:00 with the intensity of solar radiation 974 W/m2 and the lowest value of solar radiation intensity data is at 17:00 with radiation intensity value sun 170 W/m2.Keywords: Data of solar radiation intensity, direct measurement and theoretical calculation, result of measurement and calculation.